(untitled) (Research, Society and Development, 2021)
Introduction: knowledge of Basic Life Support measures favors assistance in cardiopulmonary arrest, with a view to reducing the mortality rate. Objective: to analyze the effect of training in Basic Life Support for high school students. Methodology: quasi-experimental study, carried out in March 2019, in a federal public education institution, with high school students. Sociodemographic data and questions about knowledge in Basic Life Support were collected from a questionnaire previously validated by judges, which were later analyzed using the SPSS version 23.0 program. To compare the variable level of knowledge in the immediate post-test between the groups, the Mann-Whitney test was used and this same variable within the groups, in relation to the number of correct answers, was evaluated by the Wilcoxon test. Results: Basic Life Support training was effective in improving the level of knowledge, comparing the pre-test to the immediate post-test (p<0.01). However, there was no significant increase in this in the immediate post-test among students included in group 1 compared to group 2 (p=0.12). Conclusion: training in Basic Life Support, both theoretical and practical, increased the level of knowledge of high school students on this topic. It is reinforced that health education actions on this theme are extremely relevant in high schools.